2021
DOI: 10.1530/ey.18.5.10
|View full text |Cite
|
Sign up to set email alerts
|

Single cell transcriptomic analysis of human pluripotent stem cell chondrogenesis

Abstract: The therapeutic application of human induced pluripotent stem cells (hiPSCs) for cartilage regeneration is largely hindered by the low yield of chondrocytes accompanied by unpredictable and heterogeneous off-target differentiation of cells during chondrogenesis. Here, we combine bulk RNA sequencing, single cell RNA sequencing, and bioinformatic analyses, including weighted gene co-expression analysis (WGCNA), to investigate the gene regulatory networks regulating hiPSC differentiation under chondrogenic condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Indeed, our study is also not the first use of WGCNA to detect gene-gene relatedness in scRNAseq data. WGCNA has been utilised to identify gene modules associated with the activation of neuronal stem cells (Luo et al, 2015) and human induced pluripotent stem cells (Wu et al, 2021), however, like our own study, these studies did not utilise expression from individual cells as the input for WGCNA.…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, our study is also not the first use of WGCNA to detect gene-gene relatedness in scRNAseq data. WGCNA has been utilised to identify gene modules associated with the activation of neuronal stem cells (Luo et al, 2015) and human induced pluripotent stem cells (Wu et al, 2021), however, like our own study, these studies did not utilise expression from individual cells as the input for WGCNA.…”
Section: Discussionmentioning
confidence: 88%
“…The authors identified a chondrogenic gene subset containing 1172 entities, whose functional characterisation promises to harness the potential of MSCs for cartilage tissue engineering. The same laboratory has recently published a paper on chondrogenic differentiation of hiPSCs using bulk and single-cell RNA sequencing and identified gene regulatory networks regulating chondrogenesis (36). Temporal changes in the transcriptome of human embryonic stem cells (ESCs) during key stages of chondrogenic differentiation have also been recently published (37).…”
Section: Discussionmentioning
confidence: 99%
“…Looking at the collagen expression profile of iPSCs during chondrogenesis, COL1A1 had, by far, the highest levels by day 60, followed by COL1A2 and COL3A1 , with relatively low COL2A1 levels (36). Interestingly, iPSCs also did not express the genes encoding collagen types XVII and XX.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of omission of the cell sorting step, an equally homogeneous iPSC‐chondrocyte population can be obtained by inhibiting WNT and melanocyte inducing transcription factor (MITC) signaling during pellet cultivation, as this prevents the generation of off‐target cells such as neural cells and melanocytes. ( 59 ) Importantly, inhibition of WNT signaling prevents chondrocyte hypertrophy, ( 59 ) which is beneficial for regenerative purposes but unfavorable when creating iPSC‐chondrocyte disease models. Based on the results of a study investigating the transcriptomic landscape of human somitogenesis, a more simplified protocol was proposed by Xi and colleagues ( 60 ) First, WNT/β‐catenin signaling was activated by addition of CHIR99021 to the differentiation medium to differentiate human pluripotent stem cells through primitive streak to posterior presomitic mesoderm.…”
Section: In Vitro Differentiation Approaches For Pluripotent Stem Cellsmentioning
confidence: 99%